Proceedings of the 1st Unimed International Conference on Sport Science (UnICoSS 2019) 2020
DOI: 10.2991/ahsr.k.200305.015
|View full text |Cite
|
Sign up to set email alerts
|

The Students Perception of Anatomy Learning

Abstract: Anatomy in the Department of Physical Education, Health and Recreation (PJKR) Faculty of Sports Science (FIK), State University of Medan. The method used in this research is a descriptive method. The instrument used to collect data in the form of a questionnaire given to students who took Anatomy courses in the Department of Physical Education, Health and Recreation (PJKR) Faculty of Sports Science (FIK), State University of Medan. The study population was all PJKR students who took Anatomy courses. The resear… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 2 publications
0
1
0
Order By: Relevance
“…Research conducted at the Faculty of Medicine, Islamic University of Indonesia found that 81 out of 85 students with a percentage of 95.29% realized that remembering the anatomical structure of organs related to certain diseases, strengthens understanding of related diseases. 3 Anatomy is a basic science which is considered difficult to learn and memorize the terms. Research carried out in Florida Gulf Coast University shows that out of a total of 1328 students who took anatomy and physiology I courses, only 982 students were able to take all four of the four exams in this course.…”
Section: Introductionmentioning
confidence: 99%
“…Research conducted at the Faculty of Medicine, Islamic University of Indonesia found that 81 out of 85 students with a percentage of 95.29% realized that remembering the anatomical structure of organs related to certain diseases, strengthens understanding of related diseases. 3 Anatomy is a basic science which is considered difficult to learn and memorize the terms. Research carried out in Florida Gulf Coast University shows that out of a total of 1328 students who took anatomy and physiology I courses, only 982 students were able to take all four of the four exams in this course.…”
Section: Introductionmentioning
confidence: 99%